Prevalence and study of lipid abnormalities in nephrotic syndrome attending a tertiary hospital, Nepal - Baral, Sushil; Baral, Binaya Kumar; Joshi, Karan; Shrestha, Swarup; Raut, Kanak Bahadur; Jha, Bharat (International Journal of Research in Medical Sciences, 2018)
Background: The nephrotic syndrome is a common presentation of adult or pediatric kidney diseases characterized by proteinuria, dyslipidemia, edema and hypoalbuminemia. Mainly, two types of dyslipidemia are observed: elevated serum cholesterol alone (hypercholesterolemia) and elevation of serum cholesterol along with triglyceride (combined hyperlipidemia). Therefore, majority of patients could predispose for the development of coronary artery disease and other related complications. Methods: This was the prospective hospital-based study conducted in Tribhuvan University Teaching Hospital (TUTH), Nepal. Total sixty patients who meet the inclusive criteria were selected and enrolled from Nephrology outpatient department (OPD) and ward, attending from May 2009 till August 2010. Results: In this study, total sixty patients were enrolled who was diagnosis as primary nephrotic syndrome that was established by clinical parameters supported by renal biopsy. Minimal change glomerulonephritis was common diagnosis by renal biopsy followed by Focal segmental glomerulosclerosis (FSGS). The total serum cholesterol, TG and HDL was normal in 25%, 15%, 83.3% whereas, it is high among 75%,85% and 1.7% of the study populations. Similarly, 24hour urinary protein was >3.5gm/day in all patients. Total serum protein and albumin was normal in 18.3% and 8.3% respectively whereas, rest of the patients had low serum protein and albumin levels. TC/HDLc ratios were and among them, 70% had moderate to high risk value. Similarly, in this study, the serum cholesterol, TG and TC/HDL level was inversely correlated with low protein and albumin. Conclusions: Majority of patients have derangement of lipid profile among nephrotic syndrome patients, which could also predispose for the development of coronary artery disease.